International Humanitarian Action - Heintze, Hans-Joachim; Thielb€orger, Pierre (Springer, 2018)
NOHA (The Network on Humanitarian Action) is an international association of 12 European universities and five global partner universities. The aim of NOHA is to enhance professionalism in the humanitarian sector through education and training, research and publications, and a variety of other projects. The NOHA Joint Master’s Programme in International Humanitarian Action lies at the centre of NOHA’s activities. It is managed and executed by more than 150 academics from a range of disciplines. The process involves anthropologists, lawyers, logisticians, managers, medical experts, political scientists and sociologists coordinating and constantly refining a unique programme on humanitarian action, a subject that has not been taught at universities for all too long. Central to NOHA’s growth and evolution is a core set of principles, shared by universities and humanitarian organisations the world over. It includes values such as academic rigour, shared learning, respect for peer institutions and humility, serving as the base of a cohesive and coherent network with common principles and values. Founded in 1993, NOHA today brings together over 3000 graduates working all around the world. It publishes the International Journal of International Humanitarian Action (JIHA) and organises international conferences with renowned academics and practitioners. The NOHA programme’s first semester comprises the same five modules in all NOHA universities currently offering this degree. An equal level of knowledge after the first term is a precondition for the exchange of students among the NOHA universities in the second term. With this new textbook, we aim to strengthen the coherence of our first semester curriculum and to provide all students with a solid base of knowledge from the core modules of anthropology, law, management, public health and world politics. We believe that only a solid understanding of these five disciplines, and related fields, will enable our graduates to advance in their studies and eventually become professional humanitarian aid workers.